Interconnection of women epee fencers of different qualification indicators - Briskin, Y.; Pityn, M.; Semeryak, Z.; Vaulin, O. (SportLogia, 2015)
IIt is set that discrepancy in the structure and content of correlational connections between indicators of technical and tactical kinds of training of women epee fencers of different qualification can allow to confirm about the need of educational and training correction with use of accents on the improvement of hits accuracy without attention decrease on other kinds of training of qualified sportsmen on the stage of specialized basic development and their training level approach to model indicators of high qualified women epee fencers.